Attitudes of Consumers from Subotica toward Advertising through Sport among the Frequency of Watching Sports Events - Natasa Sekulic; Zoran Milosevic; Marina Vukotic (Journal of Anthropology of Sport and Physical Education, 2018)
This investigation was aimed at gaining relevant knowledge about the attitudes of Subotica consumers toward advertising through sport among. The sample included 168 students from Chemical, Biotechnology and Medicine Department in Subotica, divided into six subsample groups: consumers, who do not watch sports events at all, then consumers who watch sports events 1-30 minutes, next 31-60 minutes, 61-90 minutes, 91-120 minutes, as well as consumers who watch sports events more than 120 minutes during the typical day. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.00. Hence, it is interesting to highlight that it was found there are significant differences showed up between the attitudes of consumers toward advertising through sport among the frequency of watching sports events. The significant differences were found in two of three variables, while the consumers who do not watch sports events had much more negative attitudes toward advertising though sport.